The impact of Body Mass Index on the mortality of myocardial infarction patients with nonobstructive coronary arteries - Dong, Chaohui; Kacmaz, Mustafa; Schlettert, Clara; Abumayyaleh, Mohammad S. A.; Akın, Ibrahim; Hemetsberger, Rayyan; Mügge, Andreas; Aweimer, Assem; Hamdani, Nazha; El-Battrawy, Ibrahim (Clinical cardiology, 2024)
Objectives Myocardial infarction without significant stenosis or occlusion of the coronary arteries carries a high risk of recurrent major adverse cardiovascular events and poor prognosis. This study aimed to investigate the association between body mass index and outcomes in patients with a suspected myocardial infarction with nonobstructive coronary artery disease (MINOCA). Methods Patients were recruited at Bergmannsheil University Hospital from January 2010 to April 2021. The primary outcomes were in-hospital and long-term mortality. Secondary outcomes consisted of adverse events during hospitalization and during follow-up. Results A total of 373 patients were included in the study, with a mean follow-up time of 6.2 years. The patients were divided into different BMI groups: < 25 kg/m² (n = 121), 25−30 kg/m² (n = 140), and > 30 kg/m² (n = 112). In-hospital mortality was 1.7% versus 2.1% versus 4.5% (p = 0.368). However, long-term mortality tended to be higher in the < 25 kg/m² group compared to the 25−30 and > 30 kg/m² groups (log-rank p = 0.067). Subgroup analysis using Kaplan−Meier analysis showed a higher rate of cardiac cause of death in the < 25 kg/m² group compared to the 25−30 and > 30 kg/m² groups: 5.7% versus 1.1% versus 0.0% (log-rank p = 0.042). No significant differences were observed in other adverse events between the different BMI groups during hospitalization and long-term follow-up. Conclusions Patients with a BMI < 25 kg/m² who experience a suspected myocardial infarction without significant coronary artery disease may have higher all-cause mortality and cardiovascular cause of death. However, further data are needed to confirm these findings.
Online veröffentlicht: 11. September 2024
Gesehen am 13.11.2024